CNG engine based on CI engine-effects of compression ratio - 458528 Zulkarnain Sidek (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of MEchanical Engineering (Automotive)) - Universiti Teknologi Malaysia, 2003